Missão organizacional, uma questão de discurso?: por uma análise crítica - Harten, Bruno Anastassiu (2013)
Through the understanding that great corporations are political, economic and social powerful agents and that their mission statements synthesize their reason of being and existing, this study aims to unveiling the political and ideological content underlying the enterprise discourse on the missions of the largest companies of Brazil. Therefore, the mission statements disclosed in the institutional and/or investor relations homepages of the 64 companies from Ibovespa, main indicator of average share prices from the Brazilian stock market, have been analyzed. The analysis were made through the appropriation of organizational culture symbolism, the critical discourse analyses, transdisciplinary theoretical instrument aiming to understand the relation between language, power, ideology and society, and from the Foucault’s discourse perspective, understanding it as an space of struggle for stabilization of the senses, which intend to be hegemonic. The data was treated in the quantitative form, searching for the most frequent words and consequently of most relevance, and in the qualitative form, grouping it in lexical categories according to their significance and its role in organizational mission statement. The results reveal the structure underlying the mission discourse, allowing the identification of specific corporative profiles according to their discursive features. Furthermore, the paper discusses how the corporative discourse appropriates the symbolic dimension with the intention of controlling and manipulating the workers, legitimize the role of corporations in society and naturalize the precepts of neoliberal ideology, presenting the current capitalist system as the only, best and inexorable form of corporate organization and production.